Strategies for Fulfilling the Basic Needs of Circular Migrant Farmers in Wonokupang, Sidoarjo - Alung Amelia Puspita Sari; Joko Mulyono; Nurina Adi Paramitha (JUSS (Jurnal Sosial Soedirman), 2023)
The purpose of this study was to find out the strategy for fulfilling the necessities of life for the circular migrant business of vegetable farm laborers in Wonokupang Village, Sidoarjo Regency. This study uses migration theory by Everett S. Lee. The research method used is a qualitative method with a case study approach. The results of this study indicate that the strategy for fulfilling the necessities of life for the circular migrant business of vegetable farm laborers is the economy and lifestyle, working patterns in migrant places and building social networks. In addition, there are socio-economic changes experienced by circular migrant vegetable farm laborers. Then, from this migration process, there are factors behind the vegetable farm laborers doing circular migration, namely individual factors, factors of origin, factors of destination, and obstacles that exist in the area of origin and destination. From these strategies, changes, and factors, it is proven that they can fulfill the necessities of life of the circular migrant business of vegetable farming laborers.